Effect of Chemical Treatment on Mechanical and Water Absorption Properties of Kenaf-Glass Fibre Mat Reinforced Unsaturated Polyester Hybrid Composites - Abid et al., W.A. Wan (International Journal of Advanced Science and Technology, 2019)
In this study, hybrid composites of kenaf fiber mat (KFM) and glass fibre mat (GFM) reinforced unsaturated polyester (UPE) composites were prepared by using hand lay-up technique and continue with compression moulding. The KFM was chemically treated with hydrogen peroxide (H2O2) at 6% in order to improve the interfacial adhesion between fibre and UPE matrix. Fourier transform infra red (FTIR) characterization was used to investigate the changes of fibers chemical constituents after chemical treatment. Mechanical and water absorption studies of untreated and peroxide treated KFM reinforced UPE-GFM composites were characterized by flexural properties (flexural strength and modulus), water uptake and thickness swelling, respectively. The result showed that, peroxide treatment of KFM caused a significant increase in the flexural properties of UPE composites. For water absorption study, it was observed that the peroxide treated KFM showed lower water uptake and thickness swelling in comparison to those of untreated KFM filled UPE-GFM composites.